2008
DOI: 10.5194/aab-51-449-2008
|View full text |Cite
|
Sign up to set email alerts
|

ANKOM – a new instrument for the determination of fat in muscle and meat cuts – a comparison

Abstract: Abstract. The objective of this study was to compare the new fat extraction equipment ANKOMXT15 Extractor with different chemical and physical methods which are widely used to determinate the fat content of different animal tissues. In total 23 pigs and 19 cattle were included in the investigations. Different cuts of the carcasses like longissimus muscle (MLD), head, belly and breast, feet, ham, neck, loin, tenderloin and subcutaneous fats were used for this comparison. The investigation compared following thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In this study, we focused on lipid content (EE) and oxidation (FOX and TBARS), and on total moisture and ash content of the product. The larval ether extracts obtained, in this study, were lower than those reported for BSF larvae [1,6,49], which may result from the samples hydrolysis prior the extraction [50]. Therefore, we recommend that no hydrolysis should be applied on BSF prior lipid extraction in future research.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, we focused on lipid content (EE) and oxidation (FOX and TBARS), and on total moisture and ash content of the product. The larval ether extracts obtained, in this study, were lower than those reported for BSF larvae [1,6,49], which may result from the samples hydrolysis prior the extraction [50]. Therefore, we recommend that no hydrolysis should be applied on BSF prior lipid extraction in future research.…”
Section: Discussionmentioning
confidence: 65%
“…The results were the averages of 16 technical replicates per sample. The equipment was calibrated according to the Soxhlet method [ 21 ]. The protein, collagen, moisture, and fat contents were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The results were the average of 16 technical replicates per sample. The equipment was calibrated to the Soxhlet method (13). Protein, collagen, moisture, and fat content were recorded.…”
Section: Chemical Compositionmentioning
confidence: 99%